2008
DOI: 10.3748/wjg.14.6835
|View full text |Cite
|
Sign up to set email alerts
|

Micronucleus analysis in patients with colorectal adenocarcinoma and colorectal polyps

Abstract: AIM:To determine, by counting micronucleus (MN) frequencies, whether chromosomal or DNA damage have an effect on the pathogenesis of early colorectal adenocarcinoma (CRC). METHODS: We analyzed MN frequencies in 21 patients with CRC, 24 patients with colon polyps [10 neoplastic polyps (NP) and 14 non-neoplastic polyps (NNP)] and 20 normal controls. RESULTS: MN frequency was significantly increased in CRC patients and in NP patients compared with controls (3.72 ± 1.34, 3.58 ± 1.21 vs 1.97 ± 0.81, P < 0.001). How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Furthermore, healthy women with BRCA1 and BRCA2 mutations showed a higher increase in MN frequency and a higher radiation sensitivity than women without family history of breast cancer (Rothfuss et al, 2000; Trenz et al, 2003). Similar outcomes were shown in lung cancer patients with a high frequency of spontaneous MN (Guler et al, 2005), as well as in patients with pleural malignant mesothelioma (Bolognesi et al, 2002), and adenocarcinoma patients (Karaman et al, 2008). Cancer-prone patients with Bloom syndrome and ataxia telangiectasia also possess a high frequency of MN in lymphocytes (Rosin and German, 1985).…”
Section: The Fate Of Micronuclei In Cellssupporting
confidence: 65%
“…Furthermore, healthy women with BRCA1 and BRCA2 mutations showed a higher increase in MN frequency and a higher radiation sensitivity than women without family history of breast cancer (Rothfuss et al, 2000; Trenz et al, 2003). Similar outcomes were shown in lung cancer patients with a high frequency of spontaneous MN (Guler et al, 2005), as well as in patients with pleural malignant mesothelioma (Bolognesi et al, 2002), and adenocarcinoma patients (Karaman et al, 2008). Cancer-prone patients with Bloom syndrome and ataxia telangiectasia also possess a high frequency of MN in lymphocytes (Rosin and German, 1985).…”
Section: The Fate Of Micronuclei In Cellssupporting
confidence: 65%
“…Our findings suggest that this phenotype might represent the largest molecular class of hereditary CRC defined to date. Classic cytogenetic studies in PBLs from patients with colon and other cancers have noted increased micronuclei, a marker of genomic instability 3234 . Moreover, while our manuscript was under review, it was reported that lymphocytes from colon cancer patients exhibit on average greater comet sizes 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Bloom syndrome or ataxia telangiectasia, have abnormally high MN frequencies [45]. Moreover, Karaman et al [30] observed a significant increase in MN level in the lymphocytes of patients with colorectal adenocarcinoma and with neoplastic polyps. Hamurcu et al [22] showed a clear increase in the frequency of MN in peripheral lymphocytes in untreated cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…UC-associated colorectal cancer occurs as a result of genetic and molecular abnormalities, such as alterations in tumor suppressor genes, oncogenes and genes encoding DNA repair proteins, as well as by an overall loss of genomic stability, similar to that seen in sporadic colorectal cancer [14,15,29,30]. Chromosomal instability is the most frequently occurring form of genomic instability in UC-associated cancers [29].…”
Section: Discussionmentioning
confidence: 99%